The Neoclassical Determinants of Real Wage - Mehmet Ivrendi; Bulent Guloglu; Y. Hakan Yetkiner (Izmir University of Economics, Department of Economics, 2013)
This paper presents empirical evidence that the neoclassical explanation of real wage has a high explanatory power at macro level. The factor endowments explanation of wage is surprisingly rare in the literature, at least at empirical level. In this paper, using panel data from 26 OECD countries, we show that technology and factor endowments (physical capital and labor stocks) have a significant explanatory power on the determination of real wage. Based on our results, we speculate that the supply-side rather than demand-side variables may be the major source of wage differences across countries.
Keywords: J31; C23; E23; E24; 330; wage; factor endowment; inter-country wage differences; panel data; Reallohn; Lohnstruktur; Produktionsfaktor; Panel; Vergleich; OECD-Staaten